Adjustment lending and mobilization of private and public resources for growth (World Bank Washington, D.C.US, 1992)
Analyses the effects of adjustment lending on growth in incomes and on the poor. Provides evidence on the medium-term responses of investment adjustment and growth. Examines how programmes supported by adjustment lending have encouraged private investment, especially by improving the business environment. Assesses the experience of countries that received adjustment lending in reforming the level and allocation of public sector spending.
DC